A Global Comparison of Counsellor Training Programs - Schulz, William E.; Ertelt, Bernd-Joachim (Canadian Journal of Counselling and Psychotherapy, 2011)
A comparison of counsellor training programs in 16 countries was presented with relation to issues such as: occupational choice or career development, professionals or technicians, labour utilization or career satisfaction, and information or relationship. Finally, some recommendations were outlined to deal with the issues.